Are Glucagon-Like Peptide-1 (GLP-1) Receptor Agonists Central Nervous System (CNS) Penetrant: A Narrative Review - Juliana West; Maggie Li; Sabrina Wong; Gia Han Le; Kayla M. Teopiz; Kyle Valentino; Christine E. Dri; Roger S. McIntyre (Neurology and Therapy)
Abstract Introduction Glucagon-like peptide-1 (GLP-1) is an incretin hormone that modulates glucose metabolism and insulin secretion. Recent translational and clinical research has evaluated the effects of GLP-1 receptor agonists (GLP-1 RAs), a class of drugs that mimic the action of native GLP-1 in the central nervous system (CNS). In addition to the efficacy of GLP-1 for the treatment of diabetes mellitus and obesity, preliminary evidence indicates GLP-1s have neuroprotective, therapeutic, and disease modification effects for select neurodegenerative disorders (e.g. Parkinson’s disease, Alzheimer’s disease). Among the available GLP-1 RAs, relatively few have been shown to be CNS penetrant. This article synthesizes extant literature reporting on CNS penetrants of GLP-1 RAs as proxied by brain imaging studies. Where available, studies that reported on the bioavailability of GLP-1 RAs in the CNS were identified. Methods A comprehensive search of PubMed, Ovid, and Web of Science from database inception to July 2024 was conducted. Inclusion criteria were English language publications with no date restrictions, preclinical and clinical studies with participants aged 18–80 and studies which focused on GLP-1 RAs including: “Semaglutide" or "Ozempic" or "Rybelsus" or "Wegovy" or "Dulaglutide" or "Trulicity" or "Exenatide" or "Byetta" or "Bydureon" or "Liraglutide" or "Lixisenatide" or "Tirzepatide" or "Mounjaro" or "Zepbound" or "Bydureon BCise" or "Adlyxin" or "Victoza" or "Saxenda". Results We identified 14 studies that were included in this synthesis. Preclinical studies suggest that select GLP-1 RAs cross the blood–brain barrier (BBB) (i.e. liraglutide, semaglutide, and exenatide). Replicated evidence suggests that CNS penetration of GLP-1 RAs can be proxied by reported effects of GLP-1 RAs on brain connectivity in human participants. Conclusion  Preclinical studies indicate that select GLP-1 RAs are CNS penetrant; whether GLP-1 RAs reproducibly engage neural targets hypothesized to subserve dimensions of psychopathology (e.g., general cognitive functions) remains incompletely characterized.